Operations of State Joint Local Governments Accounts Arrangements in Nigeria: An Empirical Study (Global Journal of Human-Social Science, 2020)
The Constitution of the Federal Republic of Nigeria 1999, as amended, contains some provisions for the state joint local government accounts between the state and local governments alike. The issue of state joint local government accounts has been a thorny concern in local-state government relationship in the fourth republic. This situation also brought to the fore the question of local government autonomy. The experience with many Local Government Areas was that their states starve them of the statutory grants, and in the process denying them the opportunity of rendering essential services as required. The study engaged in Cooperative Federalism. Franklin D. Roosevelt was the proponent of Cooperative Federalism Theory in the early part of 1930s and acknowledges a need for cooperation between all levels of governments. The study utilized both primary and secondary sources of data. Data gathered were analyzed using descriptive and content analysis.
Keywords: democratic; development; finance; good governance; local government; state government; state joint local government accounts